Computational studies on the interactions of nanomaterials with proteins and their impacts - 安德义 苏计国 李春华 李敬源 (Chinese physics B, 2015)
The intensive concern over the biosafety of nanomaterials demands the systematic study of the mechanisms underlying their biological effects. Many of the effects of nanomaterials can be attributed to their interactions with proteins and their impacts on protein function. On the other hand, nanomaterials show potential for a variety of biomedical applications,many of which also involve direct interactions with proteins. In this paper, we review some recent computational studies on this subject, especially those investigating the interactions of carbon and gold nanomaterials. Beside hydrophobic andπ-stacking interactions, the mode of interaction of carbon nanomaterials can also be regulated by their functional groups.The coatings of gold nanomaterials similarly adjust their mode of interaction, in addition to coordination interactions with the sulfur groups of cysteine residues and the imidazole groups of histidine residues. Nanomaterials can interact with multiple proteins and their impacts on protein activity are attributed to a wide spectrum of mechanisms. These findings on the mechanisms of nanomaterial–protein interactions can further guide the design and development of nanomaterials to realize their application in disease diagnosis and treatment.